2020
DOI: 10.1186/s42825-019-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic hyperbranched polymers: synthesis, characterization and self-assembly performance

Abstract: A series of amphiphilic hyperbranched polymers (AHP-s, the "s" refers to the algebra of AHP) were synthesized by the reaction between hydroxyl-terminated hyperbranched polymers (HBP-s, the "s" refers to the algebra of HBP) and palmitoyl chloride. FTIR, NMR and GPC were used to determine the structure of AHP-s, the results showed that AHP-s exhibits core-shell structure. The thermal properties of polymers were investigated by DSC and TGA. It was found that AHP-2, AHP-3 and AHP-4 display higher thermal stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…FeCl 3 ·6H 2 O is a readily available oxidant that can initiate the polymerization of EDOT and is also an ideal hydrogen bond acceptor for DES 25 . Through theoretical analysis and experimental verification, we found that substances such as organic acids (oxalic acid and lactic acid), alcohols (ethylene glycol), and amides (urea 26 and acetamide) can act as hydrogen bond donors with FeCl 3 ·6H 2 O to construct a liquid DES system for EDOT polymerization (Figure S1, Supporting Information). Comparing these DES systems in terms of reaction rate, yield, and structural morphology of PEDOT, we find that the DES system composed of FeCl 3 ·6H 2 O and acetamide is the best for the polymerization of EDOT into PEDOT with a longer molecular chain and better crystallization (Figure S1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…FeCl 3 ·6H 2 O is a readily available oxidant that can initiate the polymerization of EDOT and is also an ideal hydrogen bond acceptor for DES 25 . Through theoretical analysis and experimental verification, we found that substances such as organic acids (oxalic acid and lactic acid), alcohols (ethylene glycol), and amides (urea 26 and acetamide) can act as hydrogen bond donors with FeCl 3 ·6H 2 O to construct a liquid DES system for EDOT polymerization (Figure S1, Supporting Information). Comparing these DES systems in terms of reaction rate, yield, and structural morphology of PEDOT, we find that the DES system composed of FeCl 3 ·6H 2 O and acetamide is the best for the polymerization of EDOT into PEDOT with a longer molecular chain and better crystallization (Figure S1).…”
Section: Resultsmentioning
confidence: 98%
“…FeCl 3 Á6H 2 O is a readily available oxidant that can initiate the polymerization of EDOT and is also an ideal hydrogen bond acceptor for DES. 25 Through theoretical analysis and experimental verification, we found that substances such as organic acids (oxalic acid and lactic acid), alcohols (ethylene glycol), and amides (urea 26 and acetamide) can act as hydrogen bond donors with FeCl 3 Á6H 2 O to construct a liquid DES system for EDOT polymerization (Figure S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 340.5 and 372.7 were the main peaks, also some small peak appeared, too. So, some reactants were in the samples [23]. The Mn of HBP-OH were 340.5 and 372.7.…”
Section: Gpc Analysismentioning
confidence: 93%
“…Supramolecular assembly is a powerful tool and delicate technique to access a great variety of nano structures for functional materials. Supramolecular assembly into highly organized soft architectures through noncovalent interactions (e.g., hydrogen bonding, electrostatic interaction, 𝜋-𝜋 interaction, host-guest interaction, and metal ligand coordination) is the most common phenomenon for various biological functions in living systems like nanofibers or fibrils, [1][2][3][4][5] DNA, [6] cellular membranes, [7] and enzymes, [8] etc. The functions of these structures are often realized by reversible or dynamical assembly among components in response to condition change, [9][10][11] such as the deformation of macrophages for phagocytosis, [12] the division of DNAbased cytoskeleton, [13,14] and dynamically morphological regulate of organelles.…”
Section: Introductionmentioning
confidence: 99%